Bovine aortic arch: clinical significance and hemodynamic evaluation. (17th September 2018) - Clerici, Graziano; Giulietti, Eleonora; Babucci, Giulia; Chaoui, Rabih
Abstract: Objective: The most common aortic arch branching variation described in literature is the common origin of the brachiocephalic trunk and left common carotid artery ("bovine arch" / type II aortic arch), with an incidence of 7.2–21.1%. The first aim of this study was to investigate the prevalence of bovine arch in the fetuses. The second aim was the hemodynamic evaluation of the epiaortic vessels. Methods: In two years we examined 742 pregnant women and it was possible to obtain a good hemodynamic evaluation in 39 patients. Among the 39 fetuses, we found 6 with bovine arch. The blood flow of all epiaortic vessels and of MCA was evaluated. Results: Among the 742 fetuses examined, the bovine aortic arch was identified in 45 patients (6.06%). The hemodynamic evaluation of the epiaortic vessels showed statistically significant differences between the bovine arch and normal aortic arch. Conclusion: The presence of bovine aortic arch in the fetus is characterized by some hemodynamical differences. They could have a possible relationship with the incidence of some pathologies in adult life. Prenatal knowledge of anatomic variants of the aortic arch can bring benefits to the individual's health for future possible cardiovascular investigations.